Hukum Berbekam Bagi Orang Yang Berpuasa Perspektif Mazhab Syafi’i Dan Mazhab Hambali - Muhammad Abdul Rasyid; Zainal Muttaqin (Interdisciplinary Explorations in Research Journal, 2023)
Abstract Fasting is an obligation for a mature Muslim as an expression of the fear of a servant of God, some things can cancel fasting such as eating, drinking, putting something into the body cavities deliberately, in this case there are differences of opinion about the abolition of fasting, bekam is a type of treatment by sucking blood from the skin to cleanse the blood from toxins and increase the flow of blood. The author is interested in two major mazhabs, the mazhab of Shafi’i and the mazbab of Hambali, which have different views on the law of fasting. This study aims to study and analyze the views of both Mazhab on the Law of Fasting for the fasting people. The results of this study found that the two mazhab have differences of opinion about the law of fasting for people who are fasting although the same use of the sohih law of the hadith, the Mazhab Shafi’i argued that fasting during fasting does not cancel the fasting with the Hadith that was preached by Ibn Abbas, but there is a makruh opinion because it can weaken the body. Meanwhile, the mazhb Hambali viewed that the fast when fasting cancelled the fast, based on the good-bye hadith of Syaddad bin Aus. Keywords: fasting, cupping, mazhab of Shafi’i, mazbab of Hambali Abstrak Puasa adalah kewajiban bagi seorang muslim yang sudah dewasa sebagai sebuah ungkapan ketakwaan seorang hamba kepada Allah, beberapa hal dapat membatalkan puasa seperti makan, minum, memasukan sesuatu kedalam rongga tubuh dengan sengaja, dalam hal ini terdapat perbedaan pendapat tentang pembatal puasa, bekam adalah jenis pengobatan dengan penghisapan darah dari kulit untuk membersihkan darah dari racun dan meningkatkan aliran darah. Penulis tertarik pada dua mazhab besar yaitu mazhab Syafi’i dan mazhab Hambali, yang mempunyai pandangan yang berbeda tentang hukum berbekam saat sedang berpuasa. Penelitian ini bertujuan untuk mengkaji dan menganalisis pandangan kedua mazhab terhadap hukum berbekam bagi orang yang sedang berpuasa. Hasil penelitian ini mendapati bahwa kedua mazhab memiliki perbedaan pendapat tentang hukum berbekam bagi orang yang sedang berpuasa meskipun sama sama menggunakan dasar hukum hadis yang sohih, mazhab Syafi’i berpendapat bahwa berbekam saat berpuasa tidak membatalkan puasa dengan dalil Hadis yang diriwayatkan Oleh Ibnu Abbas , namun ada pendapat makruh karena dapat melemahkan tubuh. Sementara itu, mazhab Hambali berpandangan bahwa berbekam saat berpuasa membatalkan puasa, didasarkan pada hadis sahabat Syaddad bin Aus. Kata Kunci: Puasa, Bekam, Mazhab Syafi’i, Mazhab Hambali This is an open access article under the CC BY-NC-SA license.